Persuasion and Recommendation System Applied to a Cognitive Assistant - Angelo COSTA; Stella HERAS; Javier PALANCA; Paulo NOVAIS; Vicente JULIÁN (Advances in Distributed Computing and Artificial Intelligence Journal, 2016)
In this paper, we present a persuasive recommendation module included in the iGenda framework. iGenda is a cognitive assistant that helps care-receivers and caregivers in the management of their activities of daily living, by resolving scheduling conflicts and promoting active aging activities. The proposed new module will allow the system to select and recommend to the users an event that potentially best suits to his/her interests (likes or medical condition). The multi-agent approach followed by the iGenda framework facilitates an easy integration of these new features. The social objective is to promote social activities and engaging the users in physical or psychological activities that improve their medical condition.